Kunci kedamaian dalam keberagaman: Menggali makna tasamuh, musawah, tawasuth, dan ukhuwah - Amaliya, Denti (Maliki Interdisciplinary Journal, 2025)
Indonesia is a country rich in diversity, including ethnicity, religion, culture, and language. This diversity can be both a potential and a challenge in maintaining social harmony. In this context, Islam offers four key principles that are essential for fostering harmony amidst diversity, namely Tasamuh (tolerance), Musawah (equality), Tawasuth (moderation), and Ukhuwah (brotherhood). This article discusses the concepts and implementation of these four values in social life, as well as their urgency in creating a peaceful and harmonious life amidst differences. Through literature reviews and examples from practices in society and educational institutions, this article emphasizes that the internalization and application of these values are crucial in preventing conflicts and building a society that respects and honors one another. These four principles must be the guiding principles in social interactions in order to achieve unity and integrity in the Indonesian nation.